PHYSICOCHEMICAL AND CHEMICAL QUALITY OF MAILSI CITY GROUNDWATER - Abbas, S.; Mashiatullah, A.; Javed, A.; Khan, M. S.; Saleem, S. (The Nucleus, 2014)
Quality of groundwater samples in Mailsi city of district Vehari was assessed using physico-chemical and chemical parameters. Twenty seven (27) groundwater samples were collected for physico-chemical and major ion analysis. Absence of carbonate ions (CO3 -2 ) in all groundwater samples indicates presence of limestone dissolution giving rise to bicarbonate. Piper diagram reveals dominance with Ca-Mg-type of water in the studied area. pH of all samples were within WHO guidelines. The mean value of Total Dissolved Solids (TDS) for Mailsi groundwater is 755.1 mg/L having a range of 272 to 1667mg/L. The TDS for majority of samples lies above the guideline values as defined by the WHO. Twenty two (22) percent samples exhibit high nitrate levels; consumption of water samples with high nitrate content may produce harmful effects in children.